Biological and structural effects of the conjugation of an antimicrobial decapeptide with saturated, unsaturated, methoxylated and branched fatty acids - Húmpola, Maria Veronica (2017)
The increasing bacterial resistance against conventional antibiotics has led to the search for new antimicrobial drugs with different modes of action. Cationic antimicrobial peptides (AMPs) and lipopeptides are promising candidates to treat infections because they act on bacterial membranes causing rapid destruction of sensitive bacteria. In this study, a decapeptide named A2 (IKQVKKLFKK) was conjugated at the N-terminus with saturated, unsaturated, methoxylated and methyl -branched fatty acids of different chain lengths (C8 – C20), the antimicrobial and structural properties of the lipopeptides being then investigated. The attachment of the fatty acid chain significantly improved the antimicrobial activity of A2 against bacteria, and so, endowed it with moderated antifungal activity against yeast strains belonging to genus Candida. Lipopeptides containing hydrocarbon chain lengths between C8 and C14 were the best antibacterial compounds (MIC = 0.7 to 5.8 μM), while the most active compounds against yeast were A2 conjugated with methoxylated and enoic fatty acids (11.1 to 83.3 μM). The improvement in antimicrobial activity was mainly related to the amphipathic secondary structure adopted by A2 lipopeptides in the presence of vesicles that mimic bacterial membranes. Peptide conjugation with long hydrocarbon chains (C12 or more), regardless of their structure, significantly increased toxicity towards eukaryotic cells, resulting in a loss of selectivity. These findings suggest that A2-derived lipopeptides are potential good candidates for the treatment of infectious diseases caused by bacteria and opportunistic pathogenic yeast belonging to genus Candida. Copyright © 2016 European Peptide Society and John Wiley & Sons, Ltd.